Inhaled Gases for Neuroprotection of Neonates: A Review - Tolaymat, Youness; Doré, Sylvain; Griffin, Hudson W.; Shih, Susana; Edwards, Mary E.; Weiss, Michael D. (Frontiers in Pediatrics, 2020)
IMPORTANCE: Hypoxic-ischemic encephalopathy (HIE) is a significant cause of morbidity and mortality in neonates. The incidence of HIE is 1 to 8 per 1000 live births in developed countries. Whole-body hypothermia reduces the risk of disability or death, but only one in eight treated infants will have normal neurological function. Inhalational gases may be promising synergistic agents due to their rapid onset and easy titratability. OBJECTIVE: To review current data on different inhaled gases with neuroprotective properties that may serve as adjunct therapies to hypothermia. EVIDENCE REVIEW: We performed a literature review using PubMed and ClinicalTrials.gov. Most articles were published between 2005 and 2017. Articles published earlier than 2005 were included when appropriate for historical perspective. FINDINGS: Based on the relevance to our topic, 107 articles were selected and reviewed. The database searches targeted preclinical and clinical studies of inhaled gases and the mechanisms of action of those agents. Although whole body cooling remains the standard of managing HIE, evidence shows that inhaled gases may improve outcome. CONCLUSIONS: Many inhaled agents have neuroprotective properties and could serve as adjunct therapy to whole body cooling. Inhaled agents are ideal due to their easy administration, titratability, and rapid onset and offset.